PhyQA : An Ontology-Based Question Answering System for Formula Identification in Physics Subject - Catherine Seng Jing, Hii; Chih How, Bong (Editorial Board of Journal of Harbin Engineering, 2025)
In today's fast-paced world, it's crucial to access accurate and relevant information, especially in physics, where complex calculations are standard. Finding answers to physics questions can be difficult and time-consuming, particularly for those without a deep understanding of the subject. This paper proposes a novel solution called PhyQA - a question-answering system that utilizes ontology in the physics domain. By leveraging the power of ontologies to provide structured knowledge about physics concepts and their relationships, PhyQA can efficiently and accurately identify calculational questions. The development of this system was motivated by the need for a tool that could help bridge the gap between the complex calculations of physics and first-time learners' understanding. PhyQA provides clear and concise answers to physics questions, making it available to a broad audience, including students, researchers, and anyone interested in the subject. Using ontologies in this system provides a new technique for organizing and structuring knowledge, allowing for a more sophisticated representation of complex concepts. Ultimately, this paper emphasizes the importance of creating a question-answering system with ontology in the physics domain. It demonstrates its potential to revolutionize how we access and understand knowledge in this subject. By providing accurate and accessible answers to calculational questions, PhyQA has the potential to impact education and research in this field significantly.